Justice Sector Services and the Poor in Jordan : Determining Needs and Priorities - Prettitore, Paul (World Bank, Washington, DC, 2013)
Understanding the demands and priorities of poor persons is important to effectively target services in the justice sector. To help enhance data, in 2012 the Department of Statistics implemented a survey of 10,000 households focusing on the justice sector the first of its kind in Jordan. The survey was administered throughout the country, covering both rural and urban areas. Its primary objective was to identify the most common types of legal disputes and the characteristics of the households and individuals involved. The survey demonstrates that the most frequent types of cases reported vary by the expenditure levels of respondents. The key areas for reform to impact poverty include: improving the quality of services in personal status cases, especially access to alimony, child support and inheritance; simplifying the process of deferring court fees for poor persons; and strengthening special services developed to address personal status issues, including the newly-established alimony fund.